Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas XI SMKS IT Marinah Al-Hidayah Medan - Sipahutar, Arsad Halomoan (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study aims to analyze students' mathematical problem solving skills. The research method used is descriptive qualitative. The subjects in this study were XI grade students of SMKS IT Marinah Al-Hidayah Medan, namely 26 people. Data collection techniques using student mathematical problem solving ability test instrument on opportunity material. The data analysis technique was carried out in three stages, namely checking the results of student answers, presenting test data and drawing conclusions from the research results. The results showed that the mathematical problem solving ability of 11th grade students of SMKS IT Marinah Al-Hidayah Medan was divided into three categories, namely high, medium and low. Students with high mathematical problem solving ability are able to fulfill the indicators of understanding the problem for all questions, planning solutions for questions number 1 and 3, carrying out plans for questions number 1 and 3 and checking back for questions number 1 and 3. Students with medium mathematical problem solving ability are able to understand the indicators of understanding the problem for all questions, planning problems for questions number 1 and 3, carrying out plans for question number 3 and checking back for problem question 3.Students with low mathematical problem solving ability are not able to understand all.